AMENDMENTS TO THE CONSTITUTION OF THE RUSSIAN FEDERATION AS THE BASIS OF IDENTITY POLICY IN THE RUSSIAN FEDERATION - O. Yu. Yakhshiyan; V. A. Volokh (Вестник университета)
The article is devoted to the consideration of amendments to the Constitution of Russia approved during the vote on July 1, 2020, which set the main parameters of identity policy in our country. Special attention is paid to the reaction of public figures, experts and representatives of the leadership of the republics within the Russian Federation. During the discussion of the amendments, there was a strong public demand to clarify and fix in the form of constitutional provisions the main content of cultural and civilizational parameters of the Russian identity. The adoption of the amendments demonstrated broad public agreement on the constitutionally defined parameters of Russian national identity. The discussion showed an ambiguous attitude of ethnic activists in the republics to the set parameters of identity policy. And the leaders of a number of republics expressed their dissenting opinion, which reflected a certain tension over the inclusion of the concept of “state-forming people”in the article on the state language.